Reconciling Environmental, Social, and Governance Commitments with Corporate Tax Strategies in Indonesia: A Systematic Review - Hanum, Naila; Ghozali, Raden Roro Diana Atika; Anandita, Rissa; Evania, Alyssa Nayla (International Conference on Vocational Business, Logistic, Accounting, Supply Chain, Tax (ICoBLAST); Vol 1, No 1 (2026): 1st ICoBLAST, 2026)
Main Objectives:   This study examines sustainable taxation practices among ESG-indexed companies in Indonesia, highlighting the paradox between declared ESG commitments and corporate tax aggressiveness.   Background Problems: ESG adoption is increasingly visible among publicly listed firms, partly driven by sustainability indices and voluntary disclosure frameworks. However, a paradox emerges while ESG should theoretically promote transparency and ethical conduct, empirical evidence indicates that some ESG-oriented firms engage in aggressive tax strategies, potentially undermining their sustainability claims. This contradiction raises critical questions about the role of ESG in emerging markets with less stringent enforcement mechanisms. Addressing this paradox is vital for policymakers, investors, and scholars seeking to align sustainability goals with genuine corporate accountability.   Novelty: Sustainable taxation refers to tax policies that support ESG goals. Although ESG companies are often seen as more committed to sustainability, their tax practices and contributions to these goals remain under-explored.   Research Methods:  A systematic literature review and thematic synthesis were conducted, supported by bibliometric mapping to identify prevailing patterns and contradictions. The review draws on peer-reviewed articles published between 2019 and 2025, focusing on ESG governance, and fiscal policy incentives within the Indonesian context.   Findings/Results: Although ESG reporting promotes transparency and enhances reputational capital, it can also serve as a legitimizing tool for earnings management and aggressive tax behavior particularly in firms under financial pressure.   Conclusion: ESG strategies may function dually as instruments for sustainability and as reputational shields. Aligning tax behavior with authentic ESG objectives requires stronger corporate governance structures, clearer regulatory frameworks, and more consistent enforcement mechanisms. Implementation Potential : In Indonesia, weak regulatory enforcement and fragmented fiscal frameworks further hinder the development of genuinely sustainable tax practices